Analysis of the Impact of Digitalization and Labor Force Participation Rate on Gross Regional Domestic Product in Indonesia - Elfrian, Ari; Putri, Novi Tri (Golden Ratio of Social Science and Education, 2025)
This study examines how digitalization and labor force participation affect Indonesia's regional gross domestic product between 2018 and 2023 and uses panel data from 34 provinces. GRDP is the dependent variable, and the independent variables are internet usage, number of merchants, and activity level. The data were obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The analysis method used is multiple regression processed with E-views 12. The research findings show that GRDP is positively and significantly influenced by internet usage, the number of merchants, and the labor force participation rate by using the selected fixed effect model. These results indicate that the availability of access and use of digital technology and the level of labor market participation are key to improving the Indonesian economy.